2006
DOI: 10.1158/1078-0432.ccr-05-1471
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Mitochondrial DNA Content in Posttreatment Salivary Rinses from Head and Neck Cancer Patients

Abstract: Purpose and Experimental Design: Alterations in mitochondrial DNA (mtDNA) sequence and content have been described in human tissues and tumors in association with smoking exposure. We did quantitative PCR analysis of cytochrome c oxidase (Cox) I and Cox II genes to measure changes in mtDNA content in pretreatment and posttreatment salivary rinses obtained from 76 patients undergoing surgical resection for primary head and neck squamous cell carcinoma. We also examined the relationship between changes in mtDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…They found that tumors at advanced stages (III and IV) had much higher mtDNA content than those at lower stages (I and II). Also, patients in the radiation therapy group carried noticeably decreased levels of mtDNA as compared to the nonradiated group (Jiang et al, 2006). Similar to head and neck cancers, Lin et al (2010) pointed out that mtDNA levels in ESCC were significantly related with tumor aggressiveness and increased in a stepwise manner from noncancerous lesions to cancerous ESCC nests and then to metastatic lymph nodes.…”
Section: Roles Of Mtdna Content Turnovers In Cancer Onset and Progresmentioning
confidence: 95%
“…They found that tumors at advanced stages (III and IV) had much higher mtDNA content than those at lower stages (I and II). Also, patients in the radiation therapy group carried noticeably decreased levels of mtDNA as compared to the nonradiated group (Jiang et al, 2006). Similar to head and neck cancers, Lin et al (2010) pointed out that mtDNA levels in ESCC were significantly related with tumor aggressiveness and increased in a stepwise manner from noncancerous lesions to cancerous ESCC nests and then to metastatic lymph nodes.…”
Section: Roles Of Mtdna Content Turnovers In Cancer Onset and Progresmentioning
confidence: 95%
“…Wardell et al observed an increased number of point mutations and deletions in patients treated with radiotherapy and chemotherapy [190]. Additionally, a decrease in mtDNA content has been reported as a result of radiotherapy in cancer patients [191]. However, another study found no evidence that radiotherapy for pediatric cancer, which resulted in scatter radiation to the ovaries, is associated with the mitochondrial genome mutation frequency in female cancer survivors and their children [192].…”
Section: Radiation Therapymentioning
confidence: 99%
“…In addition, alterations in mtDNA levels are associated with various types of cancer. An increase in the amount of mtDNA is seen in prostate cancer (tissue and plasma) (Mehra et al, 2007;Mizumachi et al, 2008), untreated head and neck cancer (saliva) (Jiang et al, 2005), thyroid cancer (tissue) (Mambo et al, 2005), pancreatic cancer (cell lines) (Jones et al, 2001), ovarian cancer (tissue) (Wang et al, 2006), and endometrial cancer (tissue) (Wang et al, 2005), while a decrease is seen in gastric cancer (tissus) (Wu et al, 2005), previously treated head and neck cancer (saliva) (Jiang et al, 2006), renal cancer (cell lines and blood) (Selvanayagam et al, 1996;Xing et al, 2008), lung cancer (Dai et al, 2013), and hepatic cancer (tissue) Yin et al, 2004;Morten et al, 2007). Thus, previous research indicates that alterations in mtDNA may play an important role in tumorigenesis, and mtDNA levels may be regulated in a tumor-specific manner.…”
Section: Introductionmentioning
confidence: 99%